The Nuclear Farnesoid X Receptor Reduces p53 Ubiquitination and Inhibits Cervical Cancer Cell Proliferation - Huang, Xiaohua; Wang, Bin; Chen, Runji; Zhong, Shuping; Gao, Fenfei; Zhang, Yanmei; Niu, Yongdong; Li, Congzhu; Shi, Ganggang (Frontiers in Cell and Developmental Biology, 2021)
The role of farnesoid X receptor (FXR) in cervical cancer and the underlying molecular mechanism remain largely unknown. Therefore, this study aimed to assess the mechanism of FXR in cervical cancer. Western blot, qRT-PCR, and immunohistochemistry demonstrated that FXR was significantly reduced in squamous cell carcinoma tissues, although there were no associations of metastasis and TNM stage with FXR. In Lenti-FXR cells obtained by lentiviral transfection, the overexpression of FXR reduced cell viability and colony formation. Compared with the Lenti-Vector groups, the overexpression of FXR induced early and late apoptosis and promoted G1 arrest. With time, early apoptosis decreased, and late apoptosis increased. In tumor xenograft experiments, overexpression of FXR upregulated small heterodimer partner (SHP), murine double minute-2 (MDM2), and p53 in the nucleus. Co-immunoprecipitation (Co-IP) showed that SHP directly interacted with MDM2, which is important to protect p53 from ubiquitination. Nutlin3a increased MDM2 and p53 amounts in the Lenti-Vector groups, without effects in the Lenti-FXR groups. Silencing SHP reduced MDM2 and p53 levels in the Lenti-FXR groups, and Nutlin3a counteracted these effects. Taken together, these findings suggest that FXR inhibits cervical cancer via upregulation of SHP, MDM2, and p53.